Profil Dan Determinan Kerentanan Kemiskinan Rumah Tangga - Achintya Widhi Adnyani; Lilik Sugiharti (Universitas Musamus,Merauke,Papua, 2019)
Concept of vulnerability to poverty appears by a presence of shocks as an important dimension of poverty. The existence of shocks lead to insecurity in household welfare. This measurement of vulnerability to poverty is trying to measure probability of households fall in to poverty in the future. This study aims to measure household vulnerability to poverty and examine its determinants on the basis of a household survey data for Indonesia. Sampel data used is secondary data from IFLS 5 (Indonesia Family Life Survey) year 2014. The measurement of vulnerability to poverty is analyzed using three stage FGLS (Feasible Generalized Least Square), while its determinant is analyzed using logit regression methods. Results of this study show that Lampung province, DKI Jakarta, Sumatera Utara, Sumatera Barat, Kalimantan Selatan, dan Nusa Tenggara Barat have a high average value of vulnerability to poverty. Moreover, Lampung Province is the most vulnerable in 2014. Furthermore, this study find that age of household head, education of household head, household size,location, saving ownership,and land ownership have a significant effect on household value of vulnerability to poverty.